The Influence Of Workload And Incentives On Courier Performance At Pt Lazada Elogistics Tasikmalaya Branch - Purnama, Rian Cahya; Rahwana, Kusuma Agdhi; Karmila, Mila (Journal of Management, Economic, and Accounting, 2024)
The purpose of this study was to determine the effect of workload and incentive on the performance case on the courier PT Lazada Elogistics Tasikmalaya Branch. The research method used in a quantitative method with with a survey approach to 120 respondents who live in Tasikmalaya city. The data analsysis technique used is multiple linear regression. Based on the results of this test, it proves that workload and incentives have a significant effect simultaneously on courier performance at PT Lazada Elogistics Tasikmalaya Branch. Based on the test results, workload partially has a significant negative effect on courier performance and incentive partially have a positive effect on courier performance PT Lazada Elogistics Tasikmalaya Branch.